Long-Run Purchasing Power Parity: Is it for Real? - MacDonald, Ronald (The Review of Economics and Statistics, 1993)
In this paper we re-examine the purchasing power parity concept using data from the recent experience with floating exchange rates. In particular, we utilise the recently developed multivariate cointegration methodology to test for a long-run relationship between exchange rates and relative prices and also to test for the proportionality of the exchange rate with respect to relative prices. In contrast to much other research, we demonstrate that there is a long-run relationship between a number of bilateral U.S. dollar exchange rates and their corresponding relative prices. The proportionality of the exchange rate to relative prices does not, however, receive support from the data. This finding may be attributable to the use of measured price series rather than the "true" series.